Study on the effect of single and mixtured of cobalt nanoparticles on the change of photosynthesis parameters and antioxidant enzymes activity of soybean seedlings glycine max (l.) merr. (DT26) - Tuan, Phan Hoang; Tam, Luu Thi; Lan Anh, Hoang Thi; Thu, Ngo Thi Hoai; Chau, Nguyen Hoai; Hong, Dang Diem (Academia Journal of Biology, 2018)
Soybean (Glycine max (L) Merr.) is one of the major crops grown worldwide for human food and animal feed. Nanotechnology is one of the most potential tools in modern agriculture to improve crop productivity. In this paper, we investigated the effect of single and mixture cobalt nanoparticles on the change of photosynthesis - related parameters and antioxidant enzyme activity of soybean Glycine max (L) Merr “DT26” at different growth stages under pilot scale. The results showed that all form of cobalt nanoparticles treatment enhanced the photosynthesis of soybean by increasing the content of chlorophyll a, Pn and the ratio of Fv/Fm. These values tended to increase and reached the maximum value at fifth trifoliate stage and then decreased at the beginning bloom stage. The activity of antioxidant enzymes such as superoxide dismutase and peroxidase (when seeds were treated with USA single colbalt nanoparticles at concentration of 16.67 mg/kg) and catalase (with USA single colbalt nanoparticles at concentration of 0.17 mg/kg) were increased in 2.11, 1.85 and 1.60 times respectively compared to the control group (without the treatment of colbalt nanoparticles) while ascorbate peroxidase was reached highest value (increased in 2.73 times) under the condition of Vietnam single colbalt nanoparticles at the dose of 0.17 mg/kg seeds. This suggests that cobalt nanoparticles treatment has generated oxidative stresses and soybean DT26 has the self-protection mechanism by increasing the activity of antioxidant enzymes in order to reduce the amount of H2O2 and O2 which accumulates in the leaf cells.